Penelitian Kepustakaan (Library Research) dalam Penelitian Pendidikan IPA - Sari, Milya; Asmendri, Asmendri (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
Thesis is a scientific paper compiled by undergraduate students to complete their education. Many methods are used by students to obtain data or information in the preparation of this thesis. This form of activity is often used by students to obtain data by conducting field research. However, this type of research cannot always be carried out, especially in a co-19 pandemic emergency. Literature research is the right way to produce scientific work. But not all students are ready to do this library research. One reason is that there are no guidelines and examples they can guide to conducting this research. So the purpose of this writing is to provide guidelines for students and lecturers to carry out library research in the field of education.